FOPID-Based Load Frequency Control of Nonlinear Multi-Area Power Systems via Mayfly Optimization Algorithm - Fathy, M.; Soliman, M. (2021 22nd International Middle East Power Systems Conference (MEPCON), 2021)
In this paper, design of fractional order proportional-integral-derivative (FOPID) controllers in nonlinear multi-area interconnected systems, is presented. A three-area test system is considered to carry out this study. Typically, each turbine has limited generation rate constrain (GRC), while nonlinear performance of governor is described by its dead band (DB). Time delays imposed by signal telemetry are considered as well. Mayfly optimization algorithm (MOA) is proposed to compute the optimum parameters of FOPIDs, while minimizing a time domain based objective function. The system time response stimulated by step-load perturbation (SLP) is quantized using common ITAE index. The proposed design is compared to other designs optimized using different intelligent algorithms where the superiority of the proposed is emphasized. Robustness test based on Hermite-Biehler theorem showed that system is stable subject to parametric-uncertainties.